1974
DOI: 10.1063/1.1682481
|View full text |Cite
|
Sign up to set email alerts
|

Ground and excited states of Ne2 and Ne2+. I. Potential curves with and without spin-orbit coupling

Abstract: Ab initio configuration-interaction calculations on ground-state Ne2, the excited Σu,g+1,3 and 1,3Πu,g states of Ne2 formed from Ne(3s; 1,3P) and Ne(1S), and the Σu,g+2 and 2Πu,g states of Ne2+ have been carried out. The dissociation energies of the Σu+1,3 excited states of Ne2 were found to be considerably smaller than that of the corresponding molecular ion. Potential maxima were found in the attractive interactions of the excited Ne2 molecule. A semiempirical model, based on the observed atomic splittings, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
165
0
5

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(176 citation statements)
references
References 24 publications
6
165
0
5
Order By: Relevance
“…The decay of the plume emission was not of single exponential type, owing to the dependence of the emission lifetime on the vibrational level of the excimers (Cohen & Schneider 1974). Detailed analysis showed that most of the desorbed excimers were in the highest vibrational level, suggesting that the desorption process is much faster than vibrational relaxation.…”
Section: Excimer Desorptionmentioning
confidence: 94%
“…The decay of the plume emission was not of single exponential type, owing to the dependence of the emission lifetime on the vibrational level of the excimers (Cohen & Schneider 1974). Detailed analysis showed that most of the desorbed excimers were in the highest vibrational level, suggesting that the desorption process is much faster than vibrational relaxation.…”
Section: Excimer Desorptionmentioning
confidence: 94%
“…Since C 6 is approximately proportional to the atoms volume, 10 we estimate its value from theoretical work on excited molecular states of Ne 2 published by Cohen and Schneider. 29 We obtain C 6 Ϸ58.3 eV Å 6 for Ar dimers in electronically excited molecular states correlated with the atomic 1 P 1 energy level.…”
Section: ͑4͒mentioning
confidence: 99%
“…Since we want to address spectral regions close to the line center, we also incorporated SO coupling within a variant of the atom-inmolecule-like scheme introduced by Cohen & Schneider (1974). This scheme relies on a monoelectronic formulation of the spinorbit coupling operator…”
Section: K-h 2 Diatomic Potentials Including Spin-orbit Couplingmentioning
confidence: 99%
“…We used the molecular-structure calculations performed by Pascale (1983) for the adiabatic potentials of alkali-metal-He systems, and by Rossi & Pascale (1985) for the molecular potentials of alkali-H 2 systems. For that purpose, the fine structure was included in these potentials within the atom-in-molecule-like scheme introduced by Cohen & Schneider (1974) (see Sect. 2).…”
Section: Spectral Line Parametersmentioning
confidence: 99%